일반화 공간변조 시스템에서 채널 정보 오차를 고려한 탐색 영역 분할 수신기 - 윤학준(Hakjoon Yoon); 임창용(Changyong Im); 이경천(Kyungchun Lee) (한국정보통신학회논문지, 2019)
In this paper, we propose a low-complexity robust maximum likelihood (ML) receiver for generalized spatial modulation. The proposed receiver performs the transmit antenna partition to lower the computational loads. After we divide the transmit antenna combinations into two parts, one of which is "the likely TAC part," and the other of which is "the unlikely TAC part", based on the minimum mean square error (MMSE) filtering output. We first perform the maximum likelihood detection only in the likely TAC part. Then we evaluate the reliability of the solution found in the first search, and based its reliability we decide whether we continue the search in the unlikely TAC part. This partitioned search strategy maintains the performance of the conventional robust maximum likelihood receiver and simultaneously lowers computational loads. Through simulation, we found that our newly-proposed receiver achieves considerable gains over the conventional robust ML detector in terms of the computational loads while providing almost the same performance. 본 논문에서는 일반화 공간변조 시스템을 위한 저복잡도 강인 최대우도 수신기를 제안한다. 이 수신기는 기존의 채널 정보 오차에 강인한 최대우도 수신기의 계산량을 낮추기 위해 전송 안테나 조합 분할의 방법을 사용한다. 최소평균제곱오차 필터링 결과를 기반으로 전송 안테나 조합을 해일 가능성이 높은 영역과 낮은 영역으로 분할하고, 해일 가능성이 높은 영역에서 우선적으로 최대우도 탐색을 실시한다. 이렇게 구해진 해의 신뢰도를 판단하고, 그 결과에 따라 해일 가능성이 낮은 영역에서도 탐색을 실시할 지를 결정한다. 이와 같은 분할 탐색을 통해 기존 강인 최대우도 수신기의 성능을 유지하면서도 계산량을 크게 줄이도록 한다. 모의실험을 통해 제안 수신기가 기존 수신기의 성능을 유지하면서 계산량을 큰 폭으로 낮춘 이점을 확인하였다.